Pengaruh Tunjangan Dan Insentif Terhadap Loyalitas Kerja Karyawan (Studi Kasus Pada Karyawan CV. Putra Nusantara Sejahtera) - Achmad Syuro Al Arobi; Ahmad Subhan Mahardani; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study looks for the effect of allowances and incentives on employee loyalty to employees of CV Putra Nusantara Sejahtera. This research is quantitative in nature which aims to find a significant effect partially and simultaneously. The number of respondents used were 47 respondents, all of whom were employees of CV Putra Nusantara Sejahtera. This research method was tested with validity and reliability tests. The classical assumption test used is the normality assumption test and the multicollinearity assumption test and the heteroscedasticity assumption test. The results of this study indicate that there is a simultaneous significant effect between the variables of allowances and incentives on employee work loyalty. Partially there is a significant effect of allowances on employee work loyalty, Allowances are the most dominant variable in employee loyalty at CV Putra Nusantara Sejahtera. Keywords: Allowances, Incentives, Employee Loyalty